Microsoft Office 2010 Bible - Walkenbach(3, (BJohns; A. Bucki(3, (BLisas; Groh(3, (BMichael Rs; Tyson(3, (BHerbs; Wempen(3, (BFaithes (New Delhe Wiley, 2010)
Master the Essentials of all Office Programs Learn Shortcuts and Tricks from the Experts Explore tools for Sharing and Organizing information
Included Companion Web Site , Appendixes With Additional Information about How to Customize Office
12
Keywords: Computer Software; Microsoft Office ( Computer Software)